Odpowiedzi

2009-12-16T20:18:20+01:00
A) (8x+11)+(-3x+2)= 8x+11-3x+2= 5x+13
b) (3x+5y)-(-x_5y)= 3x+5y+x-5y= 4x
c) -(-x-y+1)-(-x-y+1)= x-y+1+x-y+1= 2x-2y+2
d) -x(-x-y)+y(-x-y)= x²+xy-yx-y
e) 4x(3x-y)-2y(2x-2y)= 12x²-4xy-2yx+4y²
f) (2x+y)(3x+4y)-(2x-y)(3x+2y)= 6x²+8xy+3yx+4y²-6x²+4xy-3yx-2y²= 12xy-2y²
2009-12-16T20:19:39+01:00
A)
(8x+11)+(-3x+2)=8x + 11 -3x + 2 = 5x + 13

b)
(3x + 5y) - (-x - 5y)= 3x + 5y + x + 5y = 4x + 10y

c)
-(-x - y + 1) - (-x - y + 1) = x + y -1 + x + y - 1 = 2x + 2y - 2

d)
-x (-x - y) + y (-x - y) = x2(do kwadratu) + xy - xy - y2 = x2 - y2

e)
4x (3x - y) - 2y (2x - 2y) = 12x - 4xy - 4xy + 2y2 = 12x - 8xy + 2y2

f)
(2x + y)(3x + 4y)-(2x - y)(3x+ 2y) = 6x + 8xy + 3xy + 4y -6x - 4xy + 3xy + 2y = 10xy+ 6y
Najlepsza Odpowiedź!
2009-12-16T20:27:10+01:00
A) (8x+11)+(-3x+2)= 8x+11+3x-2=11x+9
b) (3x+5y)-(-x_5y)=3x+5y+x+5y=4x+10y
c) -(-x-y+1)-(-x-y+1)=x+y-1+x+y-1=2x+2y-2
d) -x(-x-y)+y(-x-y)= -x*(-x)-x*(-y)+y*(-x)+y*(-y)=x²+xy-xy-y²=x²-y²
e) 4x(3x-y)-2y(2x-2y)= 4x*3x+4x*(-y)-2y*2x-2y*(-2y)=12x²-4xy-4xy+4y²=12x²+4y²-8xy
f) (2x+y)(3x+4y)-(2x-y)(3x+2y)= 2x*3x+2x*4y+y*3x+y*4y-(2x*3x+2x*2y-y*3x-y*2y)=6x²+8xy+3xy+4y²-6x²-4xy+3xy+2y²=6y²+10xy